2020
DOI: 10.4269/ajtmh.19-0616
|View full text |Cite
|
Sign up to set email alerts
|

Biologics in Leprosy: A Systematic Review and Case Report

Abstract: Tumor necrosis factor (TNF)-α inhibitors increase susceptibility to tuberculosis, but the effect of biologics on susceptibility to leprosy has not been described. Moreover, biologics may play a role in treating erythema nodosum leprosum (ENL). The objectives of this systematic review were to determine whether the development of clinical leprosy is increased in patients being treated with biologics and to assess the use of biologics in treating leprosy reactions. A systematic literature review was completed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 23 publications
0
36
0
1
Order By: Relevance
“…Ao analisar lesões neurais e o epitélio de revestimento da pele, foram observados baixos níveis de NGF e a perda de fibras nociceptivas foi associada a depleção desse fator. Logo, os níveis desse fator e consequentemente a quantidade do seu receptor de alta afinidade (TkrA) se alteram de acordo com as apresentações clínicas da hanseníase, uma vez que altos níveis foram observados na forma lepromatosa e baixos níveis na forma tuberculoide (Cogen et al, 2020). O NGF é descrito como um sinergista de ação redutora do dano tecidual em lesões neurais nas reações hansênicas promovendo regeneração ou apoptose de oligodendrócitos, células de Schwann e neurônios.…”
Section: Resultsunclassified
“…Ao analisar lesões neurais e o epitélio de revestimento da pele, foram observados baixos níveis de NGF e a perda de fibras nociceptivas foi associada a depleção desse fator. Logo, os níveis desse fator e consequentemente a quantidade do seu receptor de alta afinidade (TkrA) se alteram de acordo com as apresentações clínicas da hanseníase, uma vez que altos níveis foram observados na forma lepromatosa e baixos níveis na forma tuberculoide (Cogen et al, 2020). O NGF é descrito como um sinergista de ação redutora do dano tecidual em lesões neurais nas reações hansênicas promovendo regeneração ou apoptose de oligodendrócitos, células de Schwann e neurônios.…”
Section: Resultsunclassified
“…Although more expensive than corticosteroids, anti‐TNFα are increasingly used in developing countries. Infliximab and etanercept have already shown efficacy in ENL management 10 . When comparing secukinumab to prednisolone in RR, Debdeep reported similar efficacy and recurrence rates but fewer side effects, meaning secukinumab could be used as an alternative to prednisolone 11 .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Tumour necrosis factor inhibitor biologicals have been reported to be effective in management of erythema nodosum leprosum in few reports. [7][8][9][10][11] Faber et al showed good and sustained response in one patient of erythema nodosum leprosum following three doses of infliximab. 8 We chose etanercept due to its easy availability in our hospital low treatment cost.…”
Section: Sirmentioning
confidence: 99%